The Kalesang Values Contribution to the Students’ Success in the Faculty of Theology of Indonesian Christian University in the Moluccas (UKIM) Ambon - Claartje Pattinama (JICSA : Journal of Islamic Civilization in Southeast Asian, 2016)
The successful student of the Faculty of Theology in completing  his or her  study for becoming   a priest as his or her goal is determined  by several factors, such as: cultures,  Ambonese family traditions, motivations and commitments.Cultures and family traditions influence the success in completing his or her study to achieve his or her goal  for becoming a priest.  A student  who has hereditary priest in his or her family will be encouraged strongly by the family to become a priest.  To Ambonese people, becoming a priest is  considered to be a prestige.  Not only the priest but also his or her whole  family  are proud of becoming priests, even though they only receive lower salary compared to the salary of a state officer.   They will not mind to  receive lower salary as a priest in the world because they believe that they will have a big salary in heaven.  The kind of belief is rooted in the culture or Ambonese belief that glorying God has to be the first priority in everything they do.  The second priority is respecting  their parents or their ancestors who want  their next generations to follow their steps for working and serving God as  priests.